2017
DOI: 10.1186/s13046-017-0647-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor interaction between valproic acid, capecitabine and radiotherapy in colorectal cancer: critical role of p53

Abstract: BackgroundRecurrence with distant metastases has become the predominant pattern of failure in locally advanced rectal cancer (LARC), thus the integration of new antineoplastic agents into preoperative fluoropyrimidine-based chemo-radiotherapy represents a clinical challenge to implement an intensified therapeutic strategy.The present study examined the combination of the histone deacetylase inhibitor (HDACi) valproic acid (VPA) with fluoropyrimidine-based chemo-radiotherapy on colorectal cancer (CRC) cells.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 56 publications
(76 reference statements)
5
38
0
Order By: Relevance
“…5-fluorouracil, DNMT inhibitors, and HDAC inhibitors radiosensitize cancer cells by suppressing DNA repair activity (22)(23)(24). Fluoropyrimidine-mediated radiosensitization is extensively used in chemoradiotherapy in solid cancers (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…5-fluorouracil, DNMT inhibitors, and HDAC inhibitors radiosensitize cancer cells by suppressing DNA repair activity (22)(23)(24). Fluoropyrimidine-mediated radiosensitization is extensively used in chemoradiotherapy in solid cancers (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of resistance to 5-fluorouracil (5FU) have been described, including high levels of thymidylate synthase (TS) expression, the essential enzyme for de novo synthesis of thymidylate and subsequently DNA synthesis, and the critical target for 5FU (5). Increased levels of TS represent one of the most common and well-described 5FU resistance mechanism (6)(7)(8)(9), also in head and neck cancer models (10), and have been correlated with poorer overall patient survival in several tumors (5). Similarly, cisplatin (CDDP) resistance mechanisms are well described and are related to cell targets, uptake, and metabolism (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro studies in cell lines have shown VPA to be a radiosensitizer in melanoma, breast cancer, osteosarcoma and colorectal cancer . Several in vivo and in vitro studies as well as clinical studies have also indicated that VPA has radiosensitizing effects for gliomas and is radioprotective to normal brain tissue .…”
Section: Resultsmentioning
confidence: 99%
“…124 Recent in vitro studies in cell lines have shown VPA to be a radiosensitizer in melanoma, 125 breast cancer, 126 osteosarcoma 127 and colorectal cancer. 128 Several in vivo and in vitro studies as well as clinical studies have also indicated that VPA has radiosensitizing effects for gliomas and is radioprotective to normal brain tissue. [129][130][131] A Phase II trial of concurrent radiation therapy, temozolomide and VPA in patients with glioblastoma has reported promising treatment results, in terms of improved survival and PFS.…”
Section: Potential Use In Oncologymentioning
confidence: 99%